Variations in somatometric and somatoscopic characters among the Santhals of Dumka district, Jharkhand - Begum, Gulrukh; Narzary, Dolly (International Journal Of Community Medicine And Public Health, 2020)
Background: Baseline data collection is always very important for the planning and upliftment of any community. It determines the requirement in a more specific manner, thereby acting as an indicator, which can be used to monitor and evaluate any project. With this intention the Santhal people of Dumka in the state of Jharkhand, have been studied to prepare a baseline of their body measurements as well as their somatoscopic observations. Methods: A total of 206 adult Santhal sample has been collected, of which 111 are females and 95 are males. The data was collected with respect to 17 somatometric variables, 3 anthropometric indices and 24 somatoscopic observations. Results: The mean age of Santhal males in the present study is 35.72 years and the mean age of the females is 32.45 years. A typical Santhal of Dumka, Jharkhand is of short stature, with a hyper dolichocephalic head, females with a mesorrhine nose and the males with platyrrhine nose. The nasal index could be an adaptive strategy of survival among them. They have a euryprosopic face. Their skin colour is dark brown. Hairs are coarse, broad wavy and black in colour, which are medium in quantity. Their eyes dark brown in colour has a marked epicanthic fold. The supraorbital ridges are continuous with a broad forehead. They have a medium facial prognathism with thick lips. The Santhals of Dumka are therefore a well-adapted population of the region. Conclusions: Santhals of the present study show all the characters of Austro-Asiatic classification.